PROFESSIONAL DILEMMAS OF ORAL AND MAXILLOFACIAL SURGEONS IN A CONSERVATIVE CULTURAL CONTEXT - Mohammed Nazir Khan (Army Medical College Rawalpindi, 2019)
Objective: To explore professional dilemmas and ethically difficult situations faced by maxillofacial surgeons in conservative society of Pakistan.